Acculturation and uncertainty avoidances of the international students on the acceptance of Malay food / Nurul Amira Mohd Sanip - Mohd Sanip, Nurul Amira (2013)
Looking into the tremendous growth of international students pursuing their higher education in Malaysia, it is common for them to experienced culture shock symptom which is an excessive feeling on situation that they are not familiar yet. Despite experiencing culture shock, international students are also vulnerable to the process of acculturation towards the host country regardless of uncertainty feelings of avoidances on certain changes such as food, culture and society. Therefore, this current study investigates the influences of acculturation and uncertainty avoidance among the international students towards their acceptance on Malay food in Malaysia universities. A total of 352 students from Asia, Middle East, America, Europe and Africa have participated in this study and findings revealed that acculturation has a positive relationship with Malay food acceptance (β=.281, p< 0.001) whilst uncertainty avoidance recorded a negative relationship (β=-.165, p<0.001). As a result, study indicates that international students in Malaysia are able to accept Malay food although there is a difference in taste, texture and aroma.